EXTENT AND LEVEL OF UTILIZATION OF INFORMATION SOURCES AMONG GOAT OWNERS IN INDIA - TRIVENI DUTT, RAKESH ROY RUPASI TIWARI (Indian Journal of Animal Production and Management, 2017)
A study with the objectives to assess the pattern of information utilization was carriedout among goat owners in purposively selected states of West Bengal and Uttar Pradeshwith a sample size of 180 randomly selected respondents. The study shows the accessibilityand extent of utility of different information sources. Total Rank Order Score (TROS) showsthat informal interpersonal sources were more used by the goat owners than formalinterpersonal and mass media sources. The study reveals that informal interpersonalsources were used for all types of information such as breeding, feeding, healthcare,management and marketing of goat while formal interpersonal sources were used forhealthcare, breeding, feeding and management. The study further shows that the goatowners had low level of mass media and formal interpersonal sources utilization whileutilization of informal interpersonal sources was medium.Keywords: Goat owners, Information sources, Mass media, Total rank order score,